Extrasynaptic δ-subunit containing GABAA receptors - Ayla Arslan (Journal of Integrative Neuroscience, 2021)
γ-Aminobutyric acid type A receptors (GABAARs) are GABA gated heteropentameric chloride channels responsible for the adult brain’s primary inhibition. In specific brain cells, such as in the hippocampus, one of the subtypes of GABAARs, the δ subunit containing GABAARs (δ-GABAARs), is predominantly expressed and located in extrasynaptic or perisynaptic positions. δ-GABAARs mediate a slow constant inhibitory current called tonic inhibition. While δ-GABAARs and tonic inhibition is critical for the excitability of single neurons, accumulating data suggest that the function of δ-GABAARs are broader and includes an integrative role in the network oscillations. While these open new horizons on the neurobiology of δ-GABAARs, the complexity continues to challenge the analysis of GABAARs and their subtypes. This review will summarize the current knowledge of molecular, cellular and physiological characteristics of δ-GABAARs during health and disease.